2019
DOI: 10.1111/modl.12591
|View full text |Cite
|
Sign up to set email alerts
|

Individual Differences in L2 Speech Perception: The Role of Phonological Memory and Lipreading Ability

Abstract: The current study investigated the effects of individual differences in lipreading ability, working memory (WM), and phonological short‐term memory (PSTM) on second language (L2) speech perception. An L2 French vowel identification task was administered to 32 Australian English learners of French in audiovisual, audio‐only, and visual‐only conditions. Participants also completed tasks measuring their first language (L1) lipreading ability at the phoneme, word, and sentence level; a listening span task assessin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 87 publications
(127 reference statements)
4
17
0
Order By: Relevance
“…One reviewer suggested that the lack of audiovisual (AV) benefit in this study might be due to the order of presentation (i.e., AV before auditory-only (A-only)). This possibility is, however, unlikely as the lack of AV benefit was also observed in two other studies (Inceoglu, 2016(Inceoglu, , 2019 where the presentation order of the AV and A-only conditions were counterbalanced across participants (see also, Pereira, 2013). 6.…”
Section: Acknowledgementmentioning
confidence: 86%
See 1 more Smart Citation
“…One reviewer suggested that the lack of audiovisual (AV) benefit in this study might be due to the order of presentation (i.e., AV before auditory-only (A-only)). This possibility is, however, unlikely as the lack of AV benefit was also observed in two other studies (Inceoglu, 2016(Inceoglu, , 2019 where the presentation order of the AV and A-only conditions were counterbalanced across participants (see also, Pereira, 2013). 6.…”
Section: Acknowledgementmentioning
confidence: 86%
“…Recent work has also started to shed light on how non-native speakers perceive nasal vowels (Detey & Racine, 2015;Inceoglu, 2016Inceoglu, , 2019Marquez Martinez, 2016). Inceoglu (2016) was the first study to examine the role of visual information in the acquisition of nasal vowels.…”
Section: Previous Studies On L2 French Nasal Vowelsmentioning
confidence: 99%
“…Yet, even experienced L2 speakers might show a dissociation between the two domains, when the tasks used to assess L2 perception and production tap into di erent processing levels (e.g., Hao & de Jong, 2016;Melnik & Peperkamp, to appear;Peperkamp & Bouchon, 2011). For instance, while no relationship has been reported between L2 speech perception and production at the prelexical, acoustic-phonetic level, when using acoustic measures for L2 production accuracy (Hattori & Iverson, 2010;Schertz et al, 2015), a moderate-to-strong relationship was revealed at the phonological/lexical level, when more global perceptual (e.g., subjective) measures of perception and production accuracy (e.g., intelligibility ratings, see Evans & Alshangiti, 2018;Flege et al, 1999;Inceoglu, 2019) or tapping into similar levels of processing Flege, 1993;Flege et al, 1997Flege et al, , 1999Flege & Schmidt, 1995;Melnik & Peperkamp, to appear;Nagle, 2018) were used. In the current study, we carefully controlled for input/stimuli in exposure and during the tasks, aiming at assessing non-native perception and production at a similar prelexical, i.e., a phoneme, level; yet, the results revealed no association between the two domains.…”
Section: Discussionmentioning
confidence: 99%
“…Relatedly, previous research in L2 learning revealed no relationship (at the prelexical level) between L2 speech perception and production, when using acoustic measures of L2 production Schertz et al, 2015), as compared to when using subjective measures, e.g., intelligibility ratings, that assess L2 pronunciation beyond segmental accuracy, i.e., supra-segmental, coarticulation, etc. (Evans & Alshangiti, 2018;Flege et al, 1999;Inceoglu, 2019). Future research needs to examine ne-grained representations underlying L2 sound perception and production and their development and alignment with experience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation